Prototype Smart Garden Berbasis Internet of Things dengan Monitoring dan Kontrol Otomatis - Yasmin Nazwa Tria Azura; Aura Shafa; Obenus Ndruru; Saripah Aulia (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
This study aims to design and test a Smart Garden prototype based on the Internet of Things (IoT) for automatic plant watering monitoring and control. The system was developed to address problems associated with manual watering, which is often inconsistent, inefficient, and may lead to under-watering or over-watering conditions. The prototype integrates a capacitive soil moisture sensor, NodeMCU ESP8266 microcontroller, relay module, water pump, and the Blynk application as a remote monitoring and control interface. The system is designed to read soil moisture conditions in real time and transmit data to the microcontroller for processing. Based on predefined threshold values, the system automatically activates the water pump when the soil is dry and stops irrigation when the moisture level reaches the optimal range. The test results indicate that the system is capable of maintaining soil moisture within the required range while improving irrigation accuracy. In addition, the system helps reduce unnecessary water consumption compared to conventional manual watering methods. Therefore, the proposed IoT-based Smart Garden prototype is effective, efficient, and reliable in supporting automatic plant care and providing a practical solution for modern smart agriculture applications in household environments.